Endovascular Abdominal Aneurysm Repair in Women: What are the Differences Between the Genders? - Machado, R. (2017)
Introduction: Abdominal aortic aneurysm has a lower incidence in the female population, but a higher complication rate. It was been hypothesized that some anatomical differences of abdominal aortic aneurysm in women could be responsible for that. We proposed to analyze our data to understand the differences in the clinical and anatomical characteristics and the outcomes of patients undergoing endovascular aneurysm repair, according to gender. Methods: A retrospective analysis of patients undergoing endovascular aneurysm repair between 2001-2013 was performed. Patients were divided according gender and evaluated regarding age, atherosclerotic risk factors, aneurysm anatomic features, endograft type, anesthesic risk classification, length of stay, reinterventions and mortality. Two statistical studies were performed, first comparing women and men (Group A) and a second one comparing women and men, adjusted by age (Group B). Results: Of the 171 patients, only 5.8% (n=10) were females. Women were older (P<0.05) and the number of women with no atherosclerotic risk factor was significantly higher. The comparison adjusted by age revealed women with statistically less smoking history, less cerebrovascular disease and ischemic heart disease. Women had a trend to more complex anatomy, with more iliac intern artery aneurysms, larger aneurysm diameter and neck angulations statistically more elevated. No other variables were statistically different between age groups, neither reintervention nor mortality rates. Conclusion: Our study showed a clear difference in the clinical characteristics of women. The female population was statistically older, and when compared with men adjusted by age, had less atherosclerotic risk factors and less target organ disease. Women showed a more complex anatomy but with the same outcomes.